ADVERSE EFFECT FOLLOWING IMMUNIZATION OF COVID-19 VACCINES IN PAKISTAN - Sobhan Qadir, Muhammad Yar; Akram, Huzaifa; Ahmed, Farah; Baig, Basharat Ullah; Zia, Zaeem (Infectious Diseases Journal of Pakistan, 2023)
Background: The COVID-19 vaccines have been developed by different countries and organizations and are rays of hope toward the end of the COVID-19 pandemic. However, the concerns related to adverse effects following immunization have been a constant source of hesitancy toward vaccination. The research used cross-sectional study for four months to understand the different adverse effects following COVID-19 vaccination in Islamabad. Material and Methods: Around 400 participants were selected through a purposive sampling strategy. We included persons who received the selected COVID-19 vaccine at least 5 days ago and had a complete understanding of adverse effects. The 24th version of SPSS was used to analyze the data. Results: The results showed that among participant no one experienced life-threatening adverse effects. However, about 52.5% (n=210) of participants showed adverse effects following COVID-19 vaccination. Among the participants showing adverse effects 59% (n=72) were in the age group of 18-30 years, 64% (n=105) were in the age group of above 30 to 50 years and 34% (n=33) were in the age group of above 50- 70 years. The results show that 70% (n=100) of recipients of the Cansino vaccine reported different adverse effects and Sinopharm recipients showed least adverse effects at 43% (n=100). Conclusion: None of the participants showed any life-threatening adverse effects. However, various adverse effects were reported by recipients of all types of vaccines. Keywords: COVID-19; Adverse effect following immunization; COVID-19 vaccine